An integrated plant nutrition system (IPNS) for corn in the Mid-Atlantic USA. (16th March 2021) - Da Cunha Leme Filho, Jose Franco; Thomason, Wade E.; Evanylo, Gregory K.; Zhang, Xunzhong; Strickland, Michael S.; Chim, Bee K.; Diatta, Andre A.
Abstract: Current trends in agriculture have moved toward more sustainable cultivation systems with higher efficiency of input use. A variety of materials, derived from different resources, can serve as a crop nutrient sources. An Integrated Plant Nutrition System (IPNS) uses the combined and harmonious use of inorganic, organic and biological nutrient resources to maximize efficiency of inputs. We evaluated the effects of commercial nitrogen (N) fertilizer, humic acid compounds (HA), compost/manure teas and bioinoculants as inorganic, organic and biological resources, respectively and their synergy over three years on corn (Zea mays L.) in the Mid-Atlantic USA. The individual and combined application of HA and biofertilizer following the IPNS influenced corn height and leaf greenness to varying degrees, most likely due to biostimulant effects. In 2017, corn height, NDVI, greenness and vigor responded positively to biostimulant application to varying magnitudes and growth stages, however grain yield and nutrient content were not affected. In combined studies from 2018 and 2019 corn height was not impacted by biostimulant application but NDVI, photosynthetic efficiency, greenness and vigor were increased at different doses and corn growth stages. The combined use of HA + biofertilizer (Microlife Humic + Microgeo) was the only treatment leading to increased grain yield. This study demonstrates that the individual and combined application of HA and biofertilizer can influence corn growth and vigor at various points during the growing season. However, the current study cannot conclusively confirm that the integrated use of HA and biofertilizers (IPNS) is a better practice than the application of each compound individually.